2001
DOI: 10.1051/0004-6361:20010339
|View full text |Cite
|
Sign up to set email alerts
|

Membership, lithium, and metallicity in the young open clusters IC 2602 and IC 2391: Enlarging the sample

Abstract: Abstract. We present lithium abundances for ∼50 X-ray selected candidate members of the 30-50 Myr old open clusters IC 2602 and IC 2391. These data enlarge and extend to cooler temperatures previous Li surveys of these clusters by Stauffer et al. (1989) and Randich et al. (1997). We also give for the first time an estimate of the metallicity of the two clusters which turns out to be close to solar. Radial velocity measurements together with Hα chromospheric emission and the presence/absence of other spectrosco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
173
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 133 publications
(188 citation statements)
references
References 35 publications
(47 reference statements)
15
173
0
Order By: Relevance
“…As expected, Li abundances for stars with temperatures hotter than about 5000 K are almost constant over the time span (∼65 Myr) covered by our sample of associations (King 1998;Soderblom et al 1999;Randich et al 1997Randich et al , 2001Stauffer et al 1989;Martin & Montes 1997;Jeffries et al 2003;Balachandran et al 1988Balachandran et al , 1996Randich et al 1998;Martín 1997). On the other hand, for those associations possessing members with effective temperatures as low as to 3600 K, the observed LDPs are clearly distinguishable (right panel of Fig.…”
Section: Lithium Depletion Pattern and The Relative Agessupporting
confidence: 81%
See 2 more Smart Citations
“…As expected, Li abundances for stars with temperatures hotter than about 5000 K are almost constant over the time span (∼65 Myr) covered by our sample of associations (King 1998;Soderblom et al 1999;Randich et al 1997Randich et al , 2001Stauffer et al 1989;Martin & Montes 1997;Jeffries et al 2003;Balachandran et al 1988Balachandran et al , 1996Randich et al 1998;Martín 1997). On the other hand, for those associations possessing members with effective temperatures as low as to 3600 K, the observed LDPs are clearly distinguishable (right panel of Fig.…”
Section: Lithium Depletion Pattern and The Relative Agessupporting
confidence: 81%
“…As an additional test, we compared our abundances for IC 2391 (considered to be ArgA members) with those from Randich et al (2001). Using the EW from these authors, we also computed the Li abundances for the IC 2602 members as described above.…”
Section: Error Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…For our calculations we adopt the long-baseline Tycho-2 proper motion (Høg et al 2000) and the Tuc-Hor space motion vector from ZW00. In subjecting HD 105 to the ( Randich et al 2001) and stronger than that found in $120 Myr old Pleiades stars (Soderblom et al 1993). Finally, the X-ray luminosity of HD 105 [log (L X ) ¼ 29:4 ergs s À1 ; Cutispoto et al 2002] is similar to what is expected for early-G stars with ages of 10-100 Myr ( Briceño et al 1997).…”
Section: The Samplesupporting
confidence: 64%
“…three strong lines included in our spectral range (Ni I 664.36 nm, Fe I 666.34 nm, and V I 662.48 nm) for all target stars. We then compared them with those measured in the spectra of stars of similar temperature in IC 2391 and IC 2602, which were old enough (30-50 Myr, Randich et al 2001) to ensure that their spectra are not affected by veiling. Therefore, we did not attempt any veiling correction in our young solar-type stars.…”
Section: Introductionmentioning
confidence: 99%